The Phillips Curve and Inflation Forecasting: The Case of the Philippines - Bagsic, Cristeta B. (Philippine Management Review; Vol 11 (2004), 2016)
The Phillips curve depicts the trade-off between inflation and unemployment rate.  Studies have shown its usefulness in policymaking and most importantly in forecasting inflation.  This paper tests the Phillips curve for the Philippines and calculates the non-accelerating inflation rate of unemployment (NAIRU) using the regression results.  Robust results are obtained validating the inflation-unemployment trade-off.  From this relationship, a Philippine NAIRU of 10-11 percent is estimated.  Results likewise bear out that inflation forecasts using the Phillips curve have good tracking power and that using the skewness of the cross-sectional inflation distribution as the supply shock proxy improves the out-of-sample forecasting power of the Phillips curve.